Wet-Chemical Synthesis of InTaO4 for Photocatalytic Decomposition of Organic Contaminants in Air and Water with UV-vis Light - Ullah, Ruh; Sun, Hongqi; Wang, Shaobin; Ang, Ha Ming; Tade, Moses (American Chemical Society, 2011)
A wet-chemical technique was used to synthesize InTaO4, AgNbO3, InNbO4, and various metal doped InTaO4 catalysts. Their physicochemical properties were characterized by UV–vis diffusion reflectance spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS). Photocatalytic activities of these materials were evaluated in liquid-phase decomposition of methylene blue and phenol as well as gas-phase degradation of toluene under UV–vis light. InTaO4 exhibited higher activity than AgNbO3 and InNbO4 in photodecomposition of organic compounds in gas and liquid phases. Ni-doping could enhance the photocatalytic activities. Commercial TiO2–P25 had better activity, but Ni–InTaO4 showed more stable performance in catalytic oxidation of toluene.